Ammonia-free elastic polyester fabric with lasting quick-drying effect and preparation method of ammonia-free elastic polyester fabric
By applying a modified coating of composite microcapsules and antibacterial agents on polyester fibers, the health problems caused by spandex in traditional quick-drying fabrics are solved, and the long-lasting quick-drying effect without ammonia is achieved, which improves the fabric's Overall performance.
Patent Information
- Application Number
- CN202411519813.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-20
AI Technical Summary
Traditional quick-drying fabrics contain spandex that may cause health problems such as allergies, and it is difficult to achieve long-lasting quick-drying effect without ammonia.
Modified polyester fibers are coated with modified coatings such as composite microcapsules, water-based polyurethane and antibacterial agents, including silica, polystyrene and phase change materials, to improve the thermal energy storage and moisture-absorbing and sweating properties of the fibers while maintaining elasticity. and comfort.
It achieves a long-lasting quick-drying effect without ammonia, improves the comfort and antibacterial properties of the fabric, ensures the dryness and body temperature maintenance of human skin, while maintaining the elasticity and moisture-absorbing and sweating properties of the fabric.
Smart Images

Figure BDA0005107729700000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of polyester fabrics, and in particular to a non-spandex polyester fabric with a durable quick-drying effect and a preparation method thereof. Background Art
[0002] Fabric is the material used to make clothes. As one of the three elements of clothing, fabric can not only interpret the style and characteristics of clothing, but also directly influence the color and shape of clothing.
[0003] With the improvement of living standards, people have higher and higher functional requirements for clothing fabrics. Quick-drying fabrics have been widely used in sportswear, outdoor clothing and other fields due to their characteristics of rapid moisture absorption and perspiration removal. However, traditional quick-drying fabrics often contain elastic fibers such as spandex, which improves the elasticity of the fabric but may also cause health problems such as allergies. Therefore, the development of a polyester fabric without spandex and with a long-lasting quick-drying effect has become a current research hotspot. Summary of the invention
[0004] In order to improve the quick-drying property of polyester fabric, the present application provides a non-ammonia elastic polyester fabric with a durable quick-drying effect and a preparation method thereof.
[0005] The present application provides a non-spandex polyester fabric with a long-lasting quick-drying effect and a preparation method thereof, which adopts the following technical solutions: In the first aspect, the present application provides a non-spandex elastic polyester fabric with a long-lasting quick-drying effect, which adopts the following technical scheme: a non-spandex elastic polyester fabric with a long-lasting quick-drying effect, comprising a polyester fiber body and a polyester modified fiber, the modified polyester fiber comprising a polyester fiber body and a modified coating, the modified coating being formed by coating the modified coating on the surface of the polyester fiber body, the modified coating comprising a composite microcapsule, an aqueous polyurethane, a composite antibacterial agent and a dispersant, the composite microcapsule comprising silica, polystyrene, a phase change material and a hydrophilic modified component.
[0006] By adopting the above technical scheme, a part of the polyester fiber body is modified so that the surface of the polyester fiber body is coated with a modified coating. The modified coating is formed by attaching the modified coating to the surface of the polyester fiber body to modify the fiber body. The modified coating includes composite microcapsules, water-based polyurethane and antistatic agent. The antistatic agent can improve the antistatic effect of the fiber body. The composite microcapsules include silica, polystyrene and phase change material. After the microcapsules are prepared by coating the phase change material and attached to the polyester fiber body, the thermal energy storage performance of the polyester fiber body can be improved, so that the prepared polyester fabric has good thermal insulation performance. At the same time, the mesopores of the outer layer of the microcapsule are modified by the hydrophilic modification component, so as to give the microcapsule amphoteric properties, so that the polyester fiber body has moisture absorption and perspiration performance, thereby improving the comfort of the polyester fabric. At the same time, the polyester fabric is prepared by blending the unmodified polyester fiber with the modified polyester fiber, and the moisture absorption and perspiration performance of the polyester fabric is improved while maintaining the elasticity of the polyester fabric.
[0007] Preferably, the composite microcapsules are prepared by the following method: N-isopropylacrylamide, methacrylate tridecafluorooctyl ester, γ-methacryloxypropyltrimethoxysilane are mixed with anhydrous ethanol, and azobisisobutyronitrile is added, and the mixture is heated and stirred to react to obtain a polymer; styrene, polyvinyl pyrrolidone, phase change material, and azobisisobutyronitrile are mixed and ultrasonicated, and water is added to homogenize to obtain an emulsion system, and the emulsion system is stirred and reacted under oil bath conditions in a nitrogen environment, and washed to obtain polystyrene microcapsules; polystyrene microcapsules, hexadecyltrimethylammonium bromide, ethanol and water are mixed, and ultrasonic treatment is performed to obtain a dispersion liquid, the dispersion liquid system is adjusted to a pH value of 8-9 and the temperature is increased, and tetraethyl orthosilicate and anhydrous ethanol are added, and the mixture is stirred and reacted, and then cooled, centrifuged, and washed to obtain double-shell microcapsules; the double-shell microcapsules are ultrasonically dispersed in anhydrous ethanol, and a polymer is added, and the mixture is stirred and reacted for 12 hours to obtain a composite microcapsule.
[0008] By adopting the above technical scheme, polyvinyl pyrrolidone-modified styrene is used as the shell material, the phase change composite material is used as the core material, polyethylene microspheres coated with the phase change composite material are prepared by miniemulsion polymerization, and then the polyethylene microspheres are used as the inner core, and a silica mesoporous layer is formed on the surface of the inner core by hydrolysis of tetraethyl orthosilicate to prepare microcapsules with a double-shell structure. When sweating, the modified polyester fiber becomes hydrophilic, and sweat can be quickly adsorbed on the fabric, and the composite microcapsules containing the phase change material can store the heat in the corresponding sweat. As the temperature drops, the fabric becomes hydrophobic, and sweat can be discharged from the outer surface in time to keep the human skin dry. At the same time, the heat energy stored in the fabric is released, and the sweat will not take away the heat, so that the body temperature of the human body is maintained, further improving the overall comfort of the fabric.
[0009] Preferably, the phase change material includes n-docosane and n-eicosane.
[0010] By adopting the above technical scheme, both n-docosane and n-eicosane are good phase change materials. After being compounded as core materials, they can form a stable phase change material with thermal energy storage function, so that the polyester fabric can maintain the body temperature of the human body during moisture absorption and perspiration, thereby improving the overall comfort and thermal insulation performance of the fabric.
[0011] Preferably, the mass ratio of the polystyrene microcapsules, tetraethyl orthosilicate and polymer is 1:(1.1-1.3):0.4.
[0012] By adopting the above technical solution, preferably the mass ratio of polystyrene microcapsules, tetraethyl orthosilicate and polymer is within the above range, the stability of the prepared composite microcapsules can be further improved.
[0013] Preferably, the composite antibacterial agent comprises nano-composite zinc oxide, tannic acid and polyvinyl alcohol.
[0014] By adopting the above technical scheme, tannic acid is a polyphenol compound with functional groups such as hydroxyl and carboxyl, which can improve the overall compatibility of the system, so that zinc oxide can be more stably combined with polyester fibers. At the same time, tannic acid is also a natural antibacterial agent, which can improve the overall antibacterial properties of polyester fabrics; nano-composite zinc oxide has good chemical activity and excellent anti-ultraviolet performance, as well as good antibacterial and antistatic properties; polyvinyl alcohol is a molecular polymer with good water solubility, and the hydroxyl groups in its structure can make it stably attached to the surface of polyester fibers. At the same time, polyvinyl alcohol also has good antibacterial properties. After the three are combined, the overall antibacterial properties of the antibacterial agent can be compositely improved, so that the prepared polyester fabric has good antibacterial properties.
[0015] Preferably, the nanocomposite zinc oxide is prepared by the following method: The zinc source is mixed with dimethyl sulfoxide to obtain a zinc source solution, tetramethylammonium hydroxide is mixed with anhydrous ethanol and ultrasonically obtained as a tetramethylammonium hydroxide solution; the tetramethylammonium hydroxide solution is added to the zinc source solution, ethyl acetate is added after the reaction to obtain a white turbidity, and the white turbidity is obtained after centrifugation and drying to obtain nanocomposite zinc oxide.
[0016] By adopting the above technical scheme, the zinc source reacts slowly with the alkali agent in an organic solvent to generate zinc hydroxide, which is then slowly dehydrated and de-alcoholized for condensation to gradually form nuclei, and finally ethyl acetate is added to gradually gelatinize the zinc oxide. The prepared nano-composite zinc oxide has uniform particle size and good stability, which effectively improves the overall antibacterial performance of the antibacterial agent. At the same time, the surface of the prepared nano-composite zinc oxide has active hydroxyl groups, and the zinc oxide whiskers contact each other to form an effective three-dimensional conductive network, which promotes the transfer of charges, thereby improving the antistatic property of the polyester fiber, and thus making the prepared polyester fabric also have antistatic properties.
[0017] Preferably, the zinc source material includes zinc acetate dihydrate.
[0018] Preferably, the composite antibacterial agent is prepared by the following method: Tannic acid, polyvinyl alcohol, dimethyl sulfoxide and water are mixed, the temperature is increased and magnetic stirring is performed to obtain a premixed solution, nano-composite zinc oxide is added to the premixed solution, and the composite antibacterial agent is obtained by stirring.
[0019] By adopting the above technical scheme, polyvinyl alcohol is used as the base material, tannic acid is dissolved in dimethyl sulfoxide, and then nano-composite zinc oxide is added and stirred to prepare an antibacterial agent. During the compounding process, tannic acid molecules form hydrates in water and continuously form double bond cross-links, thereby gradually strengthening the network structure of the three, so that the antibacterial agent can be more stably bound to the surface of the polyester fiber.
[0020] Preferably, the mass ratio of tannic acid, polyvinyl alcohol and nano-composite zinc oxide is (0.7-0.9):17:1.
[0021] By adopting the above technical solution, the mass ratio of tannic acid, polyvinyl alcohol and nano-composite zinc oxide is preferably within the above range, which can further improve the stability of the prepared antibacterial agent.
[0022] In a second aspect, the present application provides a method for preparing a non-spandex polyester fabric with a durable quick-drying effect, using the following technical solution: A method for preparing a non-spandex polyester fabric with a long-lasting quick-drying effect comprises the following steps: 65-75% of polyester fiber body is used as warp yarn, and 35-25% of modified polyester fiber is used as weft yarn, which is blended into grey cloth, and the grey cloth is dried and shaped to obtain polyester fabric.
[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. After the modified coating is coated on the surface of the polyester fiber body, a modified coating is formed on the surface of the polyester fiber body. After the composite capsules and the antibacterial agent in the modified coating are attached to the surface of the polyester fiber, the prepared polyester fabric has good antibacterial properties. The composite capsules are prepared by silica, polystyrene, phase change materials and hydrophilic modified components. The phase change material is used as the core material. The mesopores of the outer layer of the prepared microcapsules are prepared by the hydrophilic modified components, thereby giving the microcapsules amphiphilic properties, so that the polyester fiber body has moisture absorption and perspiration properties, thereby improving the comfort of the prepared polyester fabric; 2. The phase change composite material is used as the core material, and polyvinyl pyrrolidone modified styrene is used as the shell material to prepare polyethylene microspheres coated with phase change materials. The polyethylene microspheres are then used as the core, and a silica mesoporous layer is formed on the surface of the core by hydrolysis of tetraethyl orthosilicate to prepare microcapsules with a double-shell structure. When sweating, the modified polyester fiber becomes hydrophilic, and sweat can be quickly adsorbed on the fabric, while the composite microcapsules containing the phase change material can store the heat in the corresponding sweat. As the temperature drops, the fabric becomes hydrophobic, and sweat can be discharged in time to keep the human skin dry. At the same time, the heat energy stored in the fabric is released to maintain the temperature of the human body, thereby improving the comfort of the fabric. 3. An antibacterial agent is prepared by combining tannic acid, nano-composite zinc oxide and polyvinyl alcohol. Tannic acid is a polyphenol compound with functional groups such as hydroxyl and carboxyl, and is also a good antibacterial agent. Nano-composite zinc oxide has good chemical activity, antistatic properties and antibacterial properties. Polyvinyl alcohol is a molecular polymer with good water solubility. After the three are combined, they can form a stable cross-linked network with improved compatibility, and can stably adhere to the surface of the polyester fiber body, thereby improving the antibacterial properties of the prepared polyester fabric. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained from commercial sources; among them, the dispersant is BYK-194N.
[0025] Example 1 Preparation of phase change material: n-docosane (CAS No.: 629-97-0) and n-eicosane (CAS No.: 112-95-8) were mixed at a mass ratio of 5:1 to obtain a phase change material.
[0026] Preparation of composite microcapsules: 7.5 g of N-isopropylacrylamide (CAS No.: 2210-25-5), 3.75 g of methacrylate tridecafluorooctyl ester (CAS No.: 2144-53-8), 0.75 g of γ-methacryloxypropyltrimethoxysilane (CAS No.: 2530-85-0) were mixed with 50 mL of anhydrous ethanol, nitrogen was introduced, and 0.03 g of azobisisobutyronitrile was added under nitrogen atmosphere, the temperature was raised to 75°C, and the mixture was stirred for reaction for 8 hours to obtain a polymer; 4.5 g of styrene, 1.5 g of polyvinyl pyrrolidone (CAS No.: 9003-39-8), 4.5 g of phase change material, and 0.3 g of azobisisobutyronitrile were mixed and ultrasonicated for 5 minutes, and then 100 mL of deionized water was added and homogenized for 15 minutes to obtain an emulsion system. The emulsion system was stirred at a speed of 400 r / min in a nitrogen environment and an oil bath at 75°C and kept reacting for 8 hours. After the reaction, petroleum ether was used to wash to obtain polystyrene microcapsules; 16 g of polystyrene microcapsules, 4 g of hexadecyltrimethylammonium bromide (CAS No.: 57-09-0), 40 g of ethanol and 120 g of deionized water were mixed and ultrasonically treated for 30 min to obtain a dispersion. 8 mL of 25% ammonia water was added to the dispersion and the dispersion system was adjusted to 8. The dispersion system was heated to 35° C., and 17.6 g of tetraethyl orthosilicate (CAS No.: 78-10-4) and 20 g of anhydrous ethanol were added to maintain the temperature. The mixture was stirred at a speed of 00 r / min for 12 hours, cooled to 25°C after the reaction, centrifuged at a speed of 8000 r / min for 10 minutes, and then washed alternately with ethanol and deionized water until the upper solution was neutral to obtain double-shell microcapsules; the double-shell microcapsules prepared above were ultrasonically dispersed in 40 mL of anhydrous ethanol, and then 6.4 g of the polymer prepared above was added, and the mixture was magnetically stirred at a speed of 400 r / min for 12 hours at 25°C to obtain composite microcapsules.
[0027] Preparation of nanocomposite zinc oxide: 300 mmol of zinc acetate dihydrate (CAS No.: 5970-45-6) and 300 mL of dimethyl sulfoxide (CAS No.: 67-68-5) are mixed to obtain a zinc source solution, 550 mmol of tetramethylammonium hydroxide (CAS No.: 75-59-2) and 100 mL of anhydrous ethanol are mixed, and the mixture is ultrasonicated at a speed of 2000 r / min for 10 minutes to obtain a tetramethylammonium hydroxide solution; the temperature of the zinc source solution is maintained at 25° C., and the pH value of the zinc source solution is adjusted to 7, the tetramethylammonium hydroxide solution is added, the reaction is carried out for 60 minutes, 3.5 g of ethyl acetate is added, a white turbid substance is obtained, and the mixture is vacuum dried at a temperature of 80° C. after centrifugation to obtain a nano-composite zinc oxide.
[0028] Preparation of composite antibacterial agent: 1.34 g of tannic acid (CAS No.: 1401-55-4), 31.79 g of polyvinyl alcohol (CAS No.: 9002-89-5), 80 g of dimethyl sulfoxide and 187 g of deionized water were mixed, and magnetic stirring was performed at a speed of 300 r / min for 4 hours in a water bath at 95°C to obtain a premixed solution. 1.87 g of nano-composite zinc oxide was added to the premixed solution, and stirred at a speed of 300 r / min for 2 hours to obtain a composite antibacterial agent.
[0029] Preparation of modified coatings: 300 g of waterborne polyurethane, 19 g of composite microcapsules, 24 g of composite antibacterial agent and 6 g of dispersant were mixed, and stirred at a speed of 200 r / min for 30 min to obtain a modified coating.
[0030] Preparation of modified fibers: The polyester fiber body is immersed in the modified coating, and after standing for 3 hours, the polyester fiber body is separated from the modified coating. The immersed polyester fiber body is then dried in an oven at 45°C for 6 hours to form a modified coating on the surface of the polyester fiber body, thereby preparing a modified fiber.
[0031] Preparation of polyester fabric: 65% of polyester fiber body is used as warp yarn, and 35% of polyester modified fiber is used as weft yarn, and they are blended at right angles to each other to form a grey cloth. The temperature is raised to 200°C, and the grey cloth is dried and shaped at a drying speed of 24Y / min. After drying, a polyester fabric is obtained.
[0032] Example 2 Preparation of phase change material: n-docosane and n-eicosane are mixed in a mass ratio of 5:1 to obtain a phase change material.
[0033] Preparation of composite microcapsules: 7.5 g of N-isopropylacrylamide, 3.75 g of methacrylate tridecafluorooctyl ester, 0.75 g of γ-methacryloxypropyltrimethoxysilane were mixed with 50 mL of anhydrous ethanol, and nitrogen was introduced. 0.03 g of azobisisobutyronitrile was added under a nitrogen atmosphere, and the temperature was raised to 75°C, and the mixture was stirred for reaction for 8 h to obtain a polymer; 4.5 g of styrene, 1.5 g of polyvinylpyrrolidone, 4.5 g of phase change material, and 0.3 g of azobisisobutyronitrile were mixed and ultrasonicated for 5 min, and 100 mL of deionized water was added, and the mixture was homogenized and dispersed for 15 min to obtain an emulsion system, and the emulsion system was stirred at a speed of 400 r / min in a nitrogen environment and an oil bath at 75°C for reaction for 8 h, and polystyrene microcapsules were obtained after washing with petroleum ether; 14.81 g of polystyrene microcapsules and 4 g of hexadecene were mixed. Alkyl trimethylammonium bromide, 40 g of ethanol and 120 g of deionized water are mixed, and ultrasonic treatment is performed for 30 minutes to obtain a dispersion liquid. 8 mL of ammonia water with a mass concentration of 25% is added to the dispersion liquid and the dispersion liquid system is adjusted to 9. The dispersion liquid system is heated to 35° C., and the temperature is maintained and 19.27 g of tetraethyl orthosilicate and 20 g of anhydrous ethanol are added. The reaction is stirred at a speed of 300 r / min for 12 hours. After the reaction, it is cooled to 25° C. and centrifuged at a speed of 8000 r / min for 10 minutes. Then, ethanol and deionized water are used to wash alternately until the upper solution is neutral to obtain double-shell microcapsules. The double-shell microcapsules prepared above are ultrasonically dispersed in 40 mL of anhydrous ethanol, and then 5.92 g of the polymer prepared above is added. The reaction is magnetically stirred at a speed of 400 r / min for 12 hours under an environment of 25° C. to obtain composite microcapsules.
[0034] Preparation of nanocomposite zinc oxide: 300 mmol of zinc acetate dihydrate and 300 mL of dimethyl sulfoxide are mixed to obtain a zinc source solution, 550 mmol of tetramethylammonium hydroxide and 100 mL of anhydrous ethanol are mixed, and the mixture is ultrasonicated at a speed of 2000 r / min for 10 minutes to obtain a tetramethylammonium hydroxide solution; the temperature of the zinc source solution is maintained at 35°C, and the pH value of the zinc source solution is adjusted to 8, the tetramethylammonium hydroxide solution is added, the reaction is carried out for 70 minutes, 3.5 g of ethyl acetate is added, a white turbid substance is obtained, and the mixture is vacuum dried at a temperature of 80°C after centrifugation to obtain a nano-composite zinc oxide.
[0035] Preparation of composite antibacterial agent: 1.7 g of tannic acid, 31.45 g of polyvinyl alcohol, 80 g of dimethyl sulfoxide and 187 g of deionized water were mixed, and magnetically stirred at a speed of 300 r / min for 4 hours in a water bath at 95°C to obtain a premixed solution. 1.85 g of nano-composite zinc oxide was added to the premixed solution, and stirred at a speed of 300 r / min for 2 hours to obtain a composite antibacterial agent.
[0036] Preparation of modified coatings: 350 g of waterborne polyurethane, 23 g of composite microcapsules, 30 g of composite antibacterial agent and 8 g of dispersant were mixed, and stirred at a speed of 200 r / min for 30 min to obtain a modified coating.
[0037] Preparation of modified fibers: The polyester fiber body is immersed in the modified coating, and after standing for 3 hours, the polyester fiber body is separated from the modified coating. The immersed polyester fiber body is then dried in an oven at 45°C for 6 hours to form a modified coating on the surface of the polyester fiber body, thereby preparing a modified fiber.
[0038] Preparation of polyester fabric: 65% of polyester fiber body is used as warp yarn, and 35% of polyester modified fiber is used as weft yarn, and they are blended at right angles to each other to form a grey cloth. The temperature is raised to 200°C, and the grey cloth is dried and shaped at a drying speed of 24Y / min. After drying, a polyester fabric is obtained.
[0039] Example 3 Preparation of phase change material: n-docosane and n-eicosane are mixed in a mass ratio of 5:1 to obtain a phase change material.
[0040] Preparation of composite microcapsules: 7.5 g of N-isopropylacrylamide, 3.75 g of methacrylate tridecafluorooctyl ester, 0.75 g of γ-methacryloxypropyltrimethoxysilane and 50 mL of anhydrous ethanol were mixed, and nitrogen was introduced. 0.03 g of azobisisobutyronitrile was added under a nitrogen atmosphere, and the temperature was raised to 75°C, and the mixture was stirred for reaction for 8 h to obtain a polymer; 4.5 g of styrene, 1.5 g of polyvinylpyrrolidone, 4.5 g of phase change material, and 0.3 g of azobisisobutyronitrile were mixed and ultrasonicated for 5 min, and 100 mL of deionized water was added, and the mixture was homogenized and dispersed for 15 min to obtain an emulsion system, and the emulsion system was stirred at a speed of 400 r / min in a nitrogen environment and an oil bath at 75°C for reaction for 8 h, and polystyrene microcapsules were obtained after washing with petroleum ether after the reaction; 15.38 g of polystyrene microcapsules and 4 g of hexadecane were added. trimethylammonium bromide, 40g of ethanol and 120g of deionized water were mixed, and ultrasonic treatment was performed for 30min to obtain a dispersion. 8mL of ammonia water with a mass concentration of 25% was added to the dispersion and the dispersion system was adjusted to 8.5. The dispersion system was heated to 35°C, and the temperature was maintained and 18.47g of tetraethyl orthosilicate and 20g of anhydrous ethanol were added. The reaction was stirred at a speed of 300r / min for 12h. After the reaction, it was cooled to 25°C, centrifuged at a speed of 8000r / min for 10min, and then washed alternately with ethanol and deionized water until the upper solution was neutral to obtain double-shell microcapsules; the double-shell microcapsules prepared above were ultrasonically dispersed in 40mL of anhydrous ethanol, and then 6.15g of the polymer prepared above was added. The reaction was magnetically stirred at a speed of 400r / min for 12h at 25°C to obtain composite microcapsules.
[0041] Preparation of nanocomposite zinc oxide: 300 mmol of zinc acetate dihydrate and 300 mL of dimethyl sulfoxide are mixed to obtain a zinc source solution, 550 mmol of tetramethylammonium hydroxide and 100 mL of anhydrous ethanol are mixed, and the mixture is ultrasonicated at a speed of 2000 r / min for 10 minutes to obtain a tetramethylammonium hydroxide solution; the temperature of the zinc source solution is maintained at 30°C, and the pH value of the zinc source solution is adjusted to 7.5, the tetramethylammonium hydroxide solution is added, the reaction is carried out for 60 minutes, 3.5 g of ethyl acetate is added, a white turbid substance is obtained, and the mixture is vacuum dried at a temperature of 80°C after centrifugation to obtain a nano-composite zinc oxide.
[0042] Preparation of composite antibacterial agent: 1.52 g of tannic acid, 31.45 g of polyvinyl alcohol, 80 g of dimethyl sulfoxide and 187 g of deionized water were mixed, and magnetically stirred at a speed of 300 r / min for 4 hours in a water bath at 95°C to obtain a premixed solution. 1.86 g of nano-composite zinc oxide was added to the premixed solution, and stirred at a speed of 300 r / min for 2 hours to obtain a composite antibacterial agent.
[0043] Preparation of modified coatings: 325 g of waterborne polyurethane, 21 g of composite microcapsules, 27 g of composite antibacterial agent and 7 g of dispersant were mixed, and stirred at a speed of 200 r / min for 30 min to obtain a modified coating.
[0044] Preparation of modified fibers: The polyester fiber body is immersed in the modified coating, and after standing for 3 hours, the polyester fiber body is separated from the modified coating. The immersed polyester fiber body is then dried in an oven at 45°C for 6 hours to form a modified coating on the surface of the polyester fiber body, thereby preparing a modified fiber.
[0045] Preparation of polyester fabric: 65% of polyester fiber body is used as warp yarn, and 35% of polyester modified fiber is used as weft yarn, and they are blended at right angles to each other to form a grey cloth. The temperature is raised to 200°C, and the grey cloth is dried and shaped at a drying speed of 24Y / min. After drying, a polyester fabric is obtained.
[0046] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing the composite microcapsules, 18.18 g of polystyrene microcapsules, 14.55 g of tetraethyl orthosilicate and 7.27 g of polymer are used.
[0047] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing the composite microcapsules, 13.33 g of polystyrene microcapsules, 21.34 g of tetraethyl orthosilicate and 5.33 g of polymer are used.
[0048] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, when preparing the composite antibacterial agent, 0.98 g of tannic acid, 32.13 g of polyvinyl alcohol, and 1.89 g of nano-composite zinc oxide are used.
[0049] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, 2.06 g of tannic acid, 31.11 g of polyvinyl alcohol and 1.83 g of nano-composite zinc oxide are used in preparing the composite antibacterial agent.
[0050] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that when preparing the composite antibacterial agent in Example 10, 60 g of dimethyl sulfoxide is added.
[0051] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that when preparing the composite antibacterial agent in Example 9, 120 g of dimethyl sulfoxide is added.
[0052] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, zinc acetate dihydrate is replaced by an equimolar amount of zinc chloride when preparing nanocomposite zinc oxide.
[0053] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 11, when preparing nano-composite zinc oxide, acetic acid dihydrate is replaced by an equimolar amount of zinc sulfate heptahydrate.
[0054] Comparative Example 1 Comparative Example 1 is based on Example 3, and in Comparative Example 1, the composite microcapsules are replaced with an equal amount of polystyrene microcapsules.
[0055] Comparative Example 2 Comparative Example 2 is based on Example 3, and in Comparative Example 2, the composite microcapsules are replaced by double-shell microcapsules.
[0056] Comparative Example 3 Comparative Example 3 is based on Example 3. In Comparative Example 3, when preparing the composite antibacterial agent, the nano-composite zinc oxide is replaced by ordinary zinc oxide.
[0057] Comparative Example 4 Comparative Example 4 is based on Example 3, and in Comparative Example 4, the composite antibacterial agent is replaced with an equal amount of tannic acid.
[0058] Comparative Example 5 Comparative Example 5 is based on Example 3, and in Comparative Example 5, the composite antibacterial agent is replaced with an equal amount of nano-composite zinc oxide.
[0059] Performance testing The following performance tests were performed on the samples of Examples 1-11 and Comparative Examples 1-5: (1) Moisture wicking performance The ambient temperature was maintained at 25°C and the relative humidity was 50%. Equal amounts of water at 40°C and 20°C were dropped on the surface of the sample. The hydrophobic angle of the sample was then tested. Each sample was tested three times and the average value was taken. The moisture absorption and perspiration performance of the sample was tested and the test results were filled in Table 1.
[0060] (2) Antibacterial performance test Taking GB / T 18830-2009 Evaluation of Anti-ultraviolet Performance of Textiles as the testing standard, the prepared fabrics were tested for anti-ultraviolet performance, and the antibacterial performance of the samples was tested 7 days later. Each sample was tested three times, and the average value was taken. The test results were filled in Table 1.
[0061] (3) Antistatic performance test The surface resistance of the fiber was tested. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.
[0062] Table 1 Performance test results of samples of Examples 1-11 and Comparative Examples 1-5 Data analysis Combined with Table 1, it can be seen that the hydrophobic angles of the sample surfaces of Examples 1-3 after being treated with water drops at 40°C are all 73° or less, indicating that when the sweat temperature contacts the fabric, the fabric is hydrophilic and can quickly absorb human sweat. The hydrophobic angles of the sample surfaces after being treated with water drops at 20°C are all 128° or more, and the fabric is hydrophobic, which promotes the fabric to discharge sweat to maintain the dryness of the fabric, indicating that the polyester fabric prepared by the present application has good moisture absorption and perspiration function and good comfort; the antibacterial rates of Escherichia coli and Staphylococcus aureus in Examples 1-3 are all 99.5% or more, indicating that the polyester fabric prepared by the present application has good antibacterial performance; the surface resistance of Examples 1-3 is only 6.5×10 6 Ω and below, indicating that the fiber prepared in the present application has good antistatic properties.
[0063] In Example 4 and Example 5, when preparing the composite microcapsules, the mass ratios of the polystyrene microcapsules, tetraethyl orthosilicate and the polymer are not within the range specified in the present application. When the content of tetraethyl orthosilicate is too little, it is difficult to form a sufficient amount of silica on the surface of the polystyrene microcapsules and to coat the polystyrene microcapsules, thereby causing the surface uniformity and stability of the prepared composite microcapsules to decrease, thereby causing the performance of the composite microcapsules to decrease. When the content of tetraethyl orthosilicate is too much, the particle size of the composite microcapsules is too large, the particle size uniformity decreases, and at the same time, the bonding effect of the polymer and silica decreases, which also affects the overall moisture absorption and perspiration performance of the microcapsule system.
[0064] In Example 6 and Example 7, when preparing the composite antibacterial agent, the mass ratios of tannic acid, polyvinyl alcohol and nano-composite zinc oxide are not within the range specified in the present application. When the content of tannic acid is too little, the hydrate formed by the tannic acid molecules in the system decreases, affecting the cross-linking of double bonds, thereby reducing the degree of cross-linking between tannic acid, polyvinyl alcohol and nano-composite zinc oxide, affecting the stability of the composite antibacterial agent; when the content of tannic acid is too much, the degree of cross-linking will be too large, the system will be too tight, affecting the moisture absorption and perspiration properties of the fiber, and at the same time, when the content of nano-composite zinc oxide decreases, the antibacterial and antistatic properties are also affected.
[0065] When the content of dimethyl sulfoxide is too little or too much, the swelling performance of the composite antibacterial agent will be affected, so that the stability of the system is reduced, so the performance of Example 8 and Example 9 are both reduced.
[0066] In Example 10 and Example 11, zinc acetate dihydrate was replaced with other zinc sources. When zinc chloride was used as the zinc source, the particle size of the prepared nanocomposite zinc oxide was too small and agglomerated in the system, affecting the overall stability of the system. When zinc sulfate heptahydrate was used as the zinc source, dimethyl sulfoxide and ethyl acetate polymerized to generate zinc sulfite impurities, affecting the overall effect of the system. Therefore, the performance of Example 10 and Example 11 was reduced.
[0067] In Comparative Example 1, polystyrene microcapsules are added. The polystyrene microcapsules that are not modified by tetraethyl orthosilicate and polymer are difficult to obtain amphoteric effects, and the hydrophobic properties are greatly reduced, so the moisture absorption and perspiration performance is greatly reduced.
[0068] In Comparative Example 2, the nano-composite zinc oxide is replaced by ordinary zinc oxide. Ordinary zinc oxide is difficult to have functional groups such as active hydroxyl groups, and its compatibility in the system is reduced. Therefore, the compatibility of zinc oxide is reduced, and its bonding performance with polyester fiber is reduced, which also affects the overall antistatic performance of the sample.
[0069] In Comparative Example 3, no polymer was used to treat the surface of the sample, and the moisture absorption and perspiration wicking performance of the system was affected.
[0070] In Comparative Example 4, the composite antibacterial agent is replaced with tannic acid. The stability of ordinary tannic acid in the system is reduced, and it is difficult to form a network cross-linking result. It is also difficult to compound multiple components to improve the overall antibacterial property of the system. At the same time, without adding nano-composite zinc oxide, the overall antistatic performance of the system is also reduced.
[0071] In Comparative Example 5, the composite antibacterial agent is replaced with nano-composite zinc oxide. Using only nano-composite zinc oxide as the antibacterial agent, the antibacterial property is difficult to be improved synergistically, the compatibility is difficult to be further improved, and the stability is reduced, which affects the overall comprehensive performance of the system.
[0072] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A non-spandex polyester fabric with a long-lasting quick-drying effect, characterized in that: It comprises a polyester fiber body and a polyester modified fiber, wherein the modified polyester fiber comprises a polyester fiber body and a modified coating, wherein the modified coating is formed by coating a modified coating on the surface of the polyester fiber body, wherein the modified coating comprises a composite microcapsule, waterborne polyurethane, a composite antibacterial agent and a dispersant, and wherein the composite microcapsule comprises silicon dioxide, polystyrene, a phase change material and a hydrophilic modified component.
2. The non-spandex polyester fabric with long-lasting quick-drying effect according to claim 1, characterized in that: The composite microcapsules are prepared by the following method: N-isopropylacrylamide, methacrylate tridecafluorooctyl ester, γ-methacryloxypropyltrimethoxysilane are mixed with anhydrous ethanol, and azobisisobutyronitrile is added, and the mixture is heated and stirred to react to obtain a polymer; styrene, polyvinyl pyrrolidone, phase change material, and azobisisobutyronitrile are mixed and ultrasonicated, and water is added to homogenize to obtain an emulsion system, and the emulsion system is stirred and reacted under oil bath conditions in a nitrogen environment, and washed to obtain polystyrene microcapsules; polystyrene microcapsules, hexadecyltrimethylammonium bromide, ethanol and water are mixed, and ultrasonic treatment is performed to obtain a dispersion liquid, the dispersion liquid system is adjusted to a pH value of 8-9 and the temperature is increased, and tetraethyl orthosilicate and anhydrous ethanol are added, and the mixture is stirred and reacted, and then cooled, centrifuged, and washed to obtain double-shell microcapsules; the double-shell microcapsules are ultrasonically dispersed in anhydrous ethanol, and a polymer is added, and the mixture is stirred and reacted for 12 hours to obtain a composite microcapsule.
3. The non-spandex polyester fabric with long-lasting quick-drying effect according to claim 2, characterized in that: The phase change material includes n-docosane and n-eicosane.
4. The non-spandex polyester fabric with long-lasting quick-drying effect according to claim 1, characterized in that: The mass ratio of the polystyrene microcapsules, tetraethyl orthosilicate and polymer is 1:(1.1-1.3):0.
4.
5. The non-spandex polyester fabric with long-lasting quick-drying effect according to claim 1, characterized in that: The composite antibacterial agent comprises nano composite zinc oxide, tannic acid and polyvinyl alcohol.
6. The non-spandex polyester fabric with long-lasting quick-drying effect according to claim 1, characterized in that: The nanocomposite zinc oxide is prepared by the following method: The zinc source is mixed with dimethyl sulfoxide to obtain a zinc source solution, tetramethylammonium hydroxide is mixed with anhydrous ethanol and ultrasonically obtained as a tetramethylammonium hydroxide solution; the tetramethylammonium hydroxide solution is added to the zinc source solution, ethyl acetate is added after the reaction to obtain a white turbidity, and the white turbidity is obtained after centrifugation and drying to obtain nanocomposite zinc oxide.
7. The non-spandex polyester fabric with long-lasting quick-drying effect according to claim 1, characterized in that: The zinc source material includes zinc acetate dihydrate.
8. The non-spandex polyester fabric with long-lasting quick-drying effect according to claim 1, characterized in that: The composite antibacterial agent is prepared by the following method: Tannic acid, polyvinyl alcohol, dimethyl sulfoxide and water are mixed, the temperature is increased and magnetic stirring is performed to obtain a premixed solution, nano-composite zinc oxide is added to the premixed solution, and the composite antibacterial agent is obtained by stirring.
9. The non-spandex polyester fabric with long-lasting quick-drying effect according to claim 1, characterized in that: The mass ratio of the tannic acid, polyvinyl alcohol and nano-composite zinc oxide is (0.7-0.9):17:
1.
10. A method for preparing the non-spandex polyester fabric with long-lasting quick-drying effect as claimed in claim 1, characterized in that: The steps include: 65-75% of polyester fiber body is used as warp yarn, and 35-25% of polyester modified fiber is used as weft yarn, which is blended into grey cloth, and the grey cloth is dried and shaped to obtain polyester fabric.
Citation Information
Cited By
Waterproof and antistatic fabric and preparation method thereof
CN120003142A
Thermal and wet comfort sensing knitted fabric and preparation method thereof
CN120245552A
Rapid perspiration and deodorization treating fluid applied to clothing fibers and preparation method of rapid perspiration and deodorization treating fluid
CN120666564A
